A Study on Adolescent Girls (16-18 Years) of Their QOL of and Its Association with Socioeconomic Status and Family Type: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The current study has thoroughly examined about the QOL of the young girls as per their age group, i.e., in the early and old age and the factors that are related to it. SES and family type are the two key elements that are considered. There is a sample of 100 girls whose age will be 16 to 18 is taken and these girls are pursuing their studies in A.M.U. Girls High school, Aligarh. Key results of the study found no major differences in QOL of the whole sample, i.e. the age group of girls who are in the younger adolescence and late adolescence. Once the study of QOL of these girls is done by taking their family type into consideration, there is an association found between two girls. A key association was observed in QOL and SES target group.